Of local and global fame: A comparative analysis of news items and audience reactions on celebrity news websites People, Heat, and HLN. (February 2014) - Van den Bulck, Hilde; Claessens, Nathalie
Worldwide, people follow global celebrities' lives almost in real time, while communities create their own celebrities, of great local fame but unknown internationally. Examining the People (USA), Heat (UK), and HLN (Flanders) websites, this article provides a quantitative framing-based content analysis of a sample of online celebrity news and the accompanying audience responses. General results show that media focus on celebrities' professional and love lives, while audiences cover more superficial topics (appearances). Further, media tend to be less and readers more judgmental in discussing celebrities. Examining global/local distinctions, HLN articles are shown to focus on global celebrities, while readers comment more on local stars. Reactions also cover more personal topics when discussing local celebrities, and both HLN articles and reactions judge global celebrities more negatively than locals. Finally, most positive parasocial relationships are maintained with local and most negative with global celebrities. The cultural proximity hypothesis can help explain these differences.